Implementasi Manajemen Berbasis Madrasah/Sekolah (MBM/MBS) Berdasarkan UU No. 20 Tahun 2003 - - Rini Setyaningsih (STAIN Bengkalis, 2019)
One of the big challenges faced by education world in Indonesia is the importance of making a change and adjustment system of national education so that can realize the more democratic education process, paying attention to kind of requirement or circumstance of area and competitor educated and also push enhancement of society participation. Therefore, Indonesia used school based management to face the challenge. MBM/ MBS represent a concept that offering autonomy at school to increase quality, efficiency and generalization of education so that can accommodate the local society desire and also braid the close of compromise between school, society and government. The characteristic of MBM cover the school mission, school activity, management strategy, resource use, role difference, human relationship, quality of all administrator and effectiveness indicator. The principal of MBM cover the commitment, readiness, involvement, institute, decision, awareness, independence and resilience. The implementation of MBM/ MBS can succeed if supported by some factor there are socialization of increasing education quality, movement of increasing education quality which governmental cymbal, mutual assistance and familiarity, head master potency, informal and formal organizational, profession organization, expectation to quality of education and management input.